Public Perceptions of The Indonesian National Police Throughcounter-Narratives in Image Rehabilitation Following The August 28, 2025, Protest Tragedy In Jakarta - Nadila Listiawati; Farida Nurfalah (Indonesian Journal Publisher, 2026)
In response to mounting public pressure and criticism on social media, the Indonesian National Police (Polri) implemented a counter-issue strategy by posting apologies, messages of empathy and details of various religious activities on the Instagram account @divisihumaspolri. This formed part of their response to the tragic incident during a demonstration involving aBrimobtactical vehicle, which resulted in the death of an online motorcycle taxi driver. This tragedy triggered a crisis of public trust in the National Police Chief. This study aims todeterminethe extent to which efforts to restore the institution’s image have been carried out using a counter-issue strategy and how the public perceives these efforts. Interview techniques, accompanied by observation of posts on the Instagram account @divisihumaspolri and a literature review, were employed in this study, which is based on a descriptive qualitative method. To ensure the validity of the research results, source triangulation was employed as a data analysis technique. The main finding of this study is that the public perceives the National Police’s communication as still being defensive and lacking transparency. The communication strategies implemented have not been fully effective in restoring the National Police’s image and public trust, asevidencedby negative public sentiment.